Within-establishment wage inequality and satisfaction - Ambra Poggi (Kiel Institute for the World Economy (IfW), 2013)
The aim of this paper is to provide fresh empirical evidence of the mechanisms through which wage inequality affects worker satisfaction. Theoretically, wages of others may affect workers' utility for two main reasons: Workers may derive well-being from their social status (comparison hypothesis) and/or they may use others wages to help predict their own future wage (information hypothesis). Both hypotheses are tested. To achieve her aims, the author models individual utility from pay as a function of a worker's own wage and the earnings of all other workers within the same establishment, and she estimates the model using British employer-employee data. Incomplete information about others wages is assumed. The author finds that the comparison effects matter. Of most interest, she provides some first evidence about a positive relation between well-being and inequality. Her results are robust within the different specifications and different definitions of the reference group.
Keywords: J28; J31; J33; C25; 330; satisfaction; comparison income; co-workers; inequality; incomplete information